CALIDENA methodology for quality infrastructure service assessment and improvement in wheat value chains. (8th April 2022) - Demissie, Mesfin; Duga, Abdi; Beshah, Birhanu; Ebinger, Frank
Wheat is one of Ethiopia's most important cereal crops in terms of the area of land allocated, the volume produced, and the number of farmers engaged in its production. About 4.7 million farmers produce 3.9 million tons of wheat across 1.6 million hectares of land. Despite the significant potential of the country, some challenges exist to attain wheat self-sufficiency. These challenges spread across the wheat value chain (WVC); wherein quality-related issues are prominent. Therefore, assessing the national quality infrastructure (NQI) service and offering mitigation schemes is a goal to pursue. To do so, this paper evaluates NQI services in the WVC and proposes an improvement mechanism using the CALIDENA methodology. Results show WVC is subjected to a significant number of quality-related issues mainly associated with conformity assessment service (calibration, certification, inspection, and testing) and standards. Finally, the paper concludes with recommendations for NQI service improvement to improve the WVC.